Heterogeneity and Architecture of Pathological Prion Protein Assemblies: Time to Revisit the Molecular Basis of the Prion Replication Process? - Igel-Egalon, Angélique (Viruses, 2019)
Prions are proteinaceous infectious agents responsible for a range of neurodegenerative diseases in animals and humans. Prion particles are assemblies formed from a misfolded, β-sheet rich, aggregation-prone isoform (PrP(Sc)) of the host-encoded cellular prion protein (PrP(C)). Prions replicate by recruiting and converting PrP(C) into PrP(Sc), by an autocatalytic process. PrP(Sc) is a pleiomorphic protein as different conformations can dictate different disease phenotypes in the same host species. This is the basis of the strain phenomenon in prion diseases. Recent experimental evidence suggests further structural heterogeneity in PrP(Sc) assemblies within specific prion populations and strains. Still, this diversity is rather seen as a size continuum of assemblies with the same core structure, while analysis of the available experimental data points to the existence of structurally distinct arrangements. The atomic structure of PrP(Sc) has not been elucidated so far, making the prion replication process difficult to understand. All currently available models suggest that PrP(Sc) assemblies exhibit a PrP(Sc) subunit as core constituent, which was recently identified. This review summarizes our current knowledge on prion assembly heterogeneity down to the subunit level and will discuss its importance with regard to the current molecular principles of the prion replication process.